World health systems : challenges and perspectives - Fried, Bruce; Gaydos, Laura M (Health Administration Press, 2002)
This sweeping text focuses on the reality of healthcare in 28 countries around the world. It is organized by wealth of each nation, and is broken up into three categories: wealthy, transitional, and very poor. From Japan to the Democratic Republic of the Congo, the authors discuss each nation\'s healthneeds, health system organization and management, the cost and price of healthcare, health resources and delivery, and future health outlook. The book addresses the types of worldwide health problems, the relationship between medical care and health, entities influencing world healthcare, and health system efficiency. Almost every chapter is written by a representative of that country, giving readers a first-hand glimpse at the conditions and health status of each country\'s population.
Keywords: Health; Quality Assurance, Health Care; poskytování zdravotní péče; Delivery of Health Care; veřejné zdravotnictví; management, organizace a řízení zdravotnictví; zajištění kvality zdravotní péče; zdraví; National Health Programs; programy národního zdraví